Activation of both transforming growth factor-β and bone morphogenetic protein signalling pathways upon traumatic brain injury restrains pro-inflammatory and boosts tissue reparatory responses of reactive astrocytes and microglia. Issue 1 (21st October 2019) - Divolis, Georgios; Stavropoulos, Athanasios; Manioudaki, Maria; Apostolidou, Anastasia; Doulou, Athanasia; Gavriil, Ariana; Dafnis, Ioannis; Chroni, Angeliki; Mummery, Christine; Xilouri, Maria; Sideras, Paschalis
Abstract: Various ligands and receptors of the transforming growth factor-β superfamily have been found upregulated following traumatic brain injury; however, the role of this signalling system in brain injury pathophysiology is not fully characterized. To address this, we utilized an acute stab wound brain injury model to demonstrate that hallmarks of transforming growth factor-β superfamily system activation, such as levels of phosphorylated Smads, ligands and target genes for both transforming growth factor-β and bone morphogenetic protein pathways, were upregulated within injured tissues. Using a bone morphogenetic protein-responsive reporter mouse model, we showed that activation of the bone morphogenetic protein signalling pathway involves primarily astrocytes that demarcate the wound area. Insights regarding the potential role of transforming growth factor-β superfamily activation in glia cells within the injured tissues were obtained indirectly by treating purified reactive astrocytes and microglia with bone morphogenetic protein-4 or transforming growth factor-β1 and characterizing changes in their transcriptional profiles. Astrocytes responded to both ligands with considerably overlapping profiles, whereas, microglia responded selectively to transforming growth factor-β1. Novel pathways, crucial for repair of tissue-injury and blood–brain barrier, such as activation of cholesterol biosynthesis and transport, production of axonal guidance and extracellular matrix components were upregulated by transforming growth factor-β1 and/or bone morphogenetic protein-4 in astrocytes. Moreover, both ligands in astrocytes and transforming growth factor-β1 in microglia shifted the phenotype of reactive glia cells towards the anti-inflammatory and tissue reparatory 'A2'-like and 'M0/M2'-like phenotypes, respectively. Increased expression of selected key components of the in vitro modulated pathways and markers of 'A2'-like astrocytes was confirmed within the wound area, suggesting that these processes could also be modulated in situ by the integrated action of transforming growth factor-β and/or bone morphogenetic protein-mediated signalling. Collectively, our study provides a comprehensive comparative analysis of transforming growth factor-β superfamily signalling in reactive astrocytes and microglia and points towards a crucial role of both transforming growth factor-β and bone morphogenetic protein pathways in modulating the inflammatory and brain injury reparatory functions of activated glia cells. Abstract : The current study provides a comprehensive comparative analysis of transforming growth factor-β and bone morphogenetic protein activation in the context of acute stab wound brain injury in glia cells and points towards a crucial role of both branches of the transforming growth factor-β superfamily signalling system in modulating the inflammatory and tissue reparatory activity of reactive astrocytes and microglia. Graphical Abstract: